Learning to be affected: Matters of pedagogy in the artists' soup kitchen. Issue 3 (23rd February 2017) - Springgay, Stephanie; Zaliwska, Zofia
Abstract: Expanding on the robust contributions by feminist new materialist scholars this essay focuses on two concepts—affect and rhythm—in order to elaborate on matters of pedagogy and a politics of attunement. If one of the key challenges that arises from feminist new materialism is that the human can no longer be taken for granted, then this prompts us to open ourselves to other ways of thinking, knowing, and doing. Being attuned to the agency of all matter offers a way of looking at how pedagogy is constituted as material, affective, and in rhythm, and this attention to the mechanisms of pedagogy can in turn affect a politics of attunement. In order to problematize an affective pedagogy we turn to a socially enagaged performance called The Artists' Soup Kitchen .